Awareness about breast cancer and breast self-examination among reproductive age group females attending outpatient department of tertiary health care hospital: a cross-sectional study - Rangari, Anchal A.; Masare, Monika S.; Khakse, Gautam M.; Thakre, Sushama S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Breast cancer (BC) is the most common type of cancer in Indian women. For every two women newly diagnosed with breast cancer, one woman died of it in India. Hence, this study was conducted to assess the awareness about breast cancer, and to assess knowledge regarding breast self-examination (BSE) among reproductive age group females. Methods: A cross-sectional study was conducted in the out-patient department (OPD) at a tertiary health care hospital from April to September 2023 among 203 females of the reproductive age group (15-49 years) using a simple random sampling technique. A self-designed, pre-tested questionnaire was used to assess awareness about breast cancer and knowledge regarding BSE. Institutional Ethics Committee approved this study. Data was analyzed with statistical package for the social sciences (SPSS) version 20.0 and Microsoft excel. Results: Study participants had a mean age of 28±8 years. Among the total participants of n=203, 93 (45.8%) were married, and 58 (28.6%) belonged to the upper socioeconomic class. A total of 175 (86.2%) women heard about BC. Among them (n=175), 133 (76.0%) women were aware of causes of BC, 89 (50.8%) knows about diagnosis, 77 (44%) had knowledge regarding treatment and 101 (57.7%) were known to preventive measures for BC. 86 (49.1%) women had knowledge about BSE, but among them only 52 (60.4%) knew proper technique and were practicing it monthly. Conclusions: Overall awareness about BC and BSE was less and measures should be taken to improve BC awareness and BSE practices.